Some aspects of accounting and management accounting during economic downturns - Dékán, Tamás (Applied Studies in Agribusiness and Commerce, 2009)
Economic slowdown and downturn creates new situation for every organisation, no one can avoid facing to new situation created by the global financial-, and economic crisis.All of the organisational function should reconsider its own role within the company due to the new circumstances, Accounting and Mangement Accounting can not be exception, but they have more complex and emphasized role in these difficult times. In the following paper I can not avoid to mention some general statement about importance of accounting and accounting principles, while there are a number of criticalaccounting and financial reporting issues that accountants and auditors should consider.In the framework of the paper I can not face with all relevant issues of the topic, but after some general statement I would like to highlight some special area regarding to management accounting, which can be more important during these challenging time for decision makers and accountants.Regarding to balance sheet analysis its important to mention current debate about fair value comparing with historical cost from accounting point of view, on the other hand from the view of management reporting system I would like to highlight the importance of working-capital indicators. More practical topic is the crucial role of budgeting and forecasting during economic downturns, and at the end I would like to show why it is more important monitoring price variance and indirect cost allocation in these uncertain business circumstances.